Rice Production Risk in Main Producing Countries 1961-2021 - Aura Dhamira; Fadilla Ristya Aminda (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Rice is an important food commodity to meet the high demand for food, especially in Asia. Most of the central producing countries of this commodity are located in Asia, and they play a significant role in supporting the availability of food for the people amidst the significant risks and uncertainties in carrying out rice farming, including the consequences of climate change and pests and diseases. This study aims to (1) find out the trend of rice production and production risks in the central producing countries over 61 years and (2) find out the risks of rice production in each of the central producing countries. This research was conducted using descriptive analysis using secondary data from 1961-2021, which was processed into tables and graphs. Meanwhile, the calculation of production risk is carried out using the coefficient of variation method. The results show that rice production in the central producing countries has a positive trend, where production increases from year to year. This is followed by a decrease in the risk of rice production every year. Vietnam is a country with the most significant rice production risk, while Cina and Brazil are countries with the lowest production risk. The application of programs proclaimed by the government, which are also adapted to the characteristics of farmers and actual conditions in the field, is expectee to minimize production risks so that optimal production can be achieved.